Oxygen Octahedral Distortions in LaMO3/SrTiO3 Superlattices. (24th April 2014) - Sanchez-Santolino, Gabriel; Cabero, Mariona; Varela, Maria; Garcia-Barriocanal, Javier; Leon, Carlos; Pennycook, Stephen J.; Santamaria, Jacobo
Abstract: In this work we study the interfaces between the Mott insulator LaMnO3 (LMO) and the band insulator SrTiO3 (STO) in epitaxially grown superlattices with different thickness ratios and different transport and magnetic behaviors. Using atomic resolution electron energy-loss spectral imaging, we analyze simultaneously the structural and chemical properties of these interfaces. We find changes in the oxygen octahedral tilts within the LaMnO3 layers when the thickness ratio between the manganite and the titanate layers is varied. Superlattices with thick LMO and ultrathin STO layers present unexpected octahedral tilts in the STO, along with a small amount of oxygen vacancies. On the other hand, thick STO layers exhibit undistorted octahedra while the LMO layers present reduced O octahedral distortions near the interfaces. These findings are discussed in view of the transport and magnetic differences found in previous studies.